Independent Curriculum Policy in Early Childhood Education Units in Indonesia - Lisnawati, Rita; Jannah, Nur Lailatul; Andika Sari, Diah (Annpublisher, 2024)
The Independent Curriculum is an innovative advancement in the Indonesian education system, namely in Early Childhood Education (PAUD). This study aims to discover the Independent Curriculum policy in PAUD (Early Childhood Education) through a literature review approach. In particular, the researcher will analyze and evaluate policies, regulations, and theories related to the definition of the Independent Curriculum in Early Childhood Education. Information is gathered from reliable sources, including scientific publications, books, and official government papers. The study's findings show that the Independent Curriculum offers PAUD the ability to tailor the curriculum to the specific needs and attributes of students, thus providing flexibility. PAUD is encouraged to develop the Pancasila Student Profile through child-centered learning, play, and exploration. This research also found several challenges in implementing the Independent Curriculum in PAUD, such as limited human resources, infrastructure, and funding. Ultimately, the Independent Curriculum has great potential to improve the quality of early childhood education in Indonesia. Nevertheless, it is crucial for some stakeholders to consistently exert their efforts to ensure the smooth and smooth implementation of the implementation process.